Development of a Web-based user orientation program for the College of Science University of the Philippines Diliman - Bobis, Evelyn N. 1964-
Data from the needs assessment questionnaires were presented in tabular form showing the frequency and their corresponding percentages. It was supplemented with linear graphs in the prsentation of the findings both in the Pretest and Posttest as well as in the system evaluation. Actual data generated from the Statistical Analysis Software was included in th Appendix for cross-referencing. The results of the study was found to be significant since the p value of the pretest and posttest is .0001 which means that there was a significant difference in the results of the Posttest after the respondents' reading of the developed web-based user orientation program. On the other hand, the results of the system evaluation revealed that the project was useful, easy to use and respondents find it more convenient.